Immune checkpoint inhibitors continuation beyond progression as second-line treatment for extensive-stage small-cell lung cancer: a real-world, multicenter analysis - Zhang, Jiao; Zi, Rui; Zhang, Hai-xia; Lv, Ye; Zhao, Lu-jun; Wang, Yan (Frontiers in Immunology, 2025)
BackgroundOptimal management of extensive-stage small-cell lung cancer (ES-SCLC) following progression on first-line (1L) chemoimmunotherapy remains undefined. This study aimed to evaluate the efficacy of immune checkpoint inhibitors (ICIs) continuation in a second-line (2L) treatment setting.MethodsA total of 211 ES-SCLC patients with disease progression after 1L chemoimmunotherapy were analyzed retrospectively after stratifying them into ICIs continuation (n = 118) and ICIs discontinuation (n = 93) cohorts. The primary endpoint was 2L overall survival (2L-OS), and the secondary endpoints included 2L progression-free survival (2L-PFS), objective response rate (2L-ORR), disease control rate (2L-DCR), and safety. Propensity score matching (PSM, 1:1) ensured balanced baseline characteristics. Survival analyses were conducted based on Kaplan-Meier curves. Univariate and multivariate Cox regression analyses were performed to identify the factors associated with 2L-PFS and 2L-OS.ResultsICIs continuation significantly improved 2L-OS (8.66 vs 7.90 months; P = 0.016) and 2L-PFS (3.92 vs. 2.15 months; P < 0.001). The benefits of ICIs continuation persisted after PSM (2L-OS: 10.31 vs. 8.95 months, P = 0.027; 2L-PFS: 4.22 vs.2.12 months, P < 0.001). In addition, the ICIs continuation group demonstrated superior tumor response (2L-ORR: 28.8% vs. 11.8%, P = 0.003; 2L-DCR: 65.3% vs. 44.1%, P = 0.002), which remained significant post-PSM. Treatment-related adverse events (AEs) were comparable between the groups, while immune-related AEs were predominantly low grade in the ICIs continuation group. Multivariate analysis revealed that baseline liver metastasis and 1L-PFS were independent risk factors for 2L-PFS and 2L-OS, whereas overweight (BMI 25.0-29.9) was an independent prognostic factor for 2L-OS. The exploratory analysis conducted for the ICIs continuation cohort revealed no significant difference in patient survival between the continuing ICIs treatment group and switching ICIs treatment group (2L-OS: P = 0.668; 2L-PFS: P = 0.346).ConclusionIn patients with ES-SCLC who exhibit disease progression after 1L chemoimmunotherapy, continuation of ICIs significantly improves survival and tumor response while achieving a manageable safety profile. Therefore, ICIs continuation may be considered a viable strategy in 2L settings.